Pengaruh Pemijatan Perineum Pada Ibu Hamil Trimester III Terhadap Kejadian Ruptur Perineum Saat Persalinan Di Klinik Yusmalinda Kecamatan Stabat Kabupaten Langkat Tahun 2022 - Lisnawati br Ritonga; Ninsah Mandala Putri Br Sembiring (Institut Nalanda, 2023)
Labor includes a physiological process that allows a series of major changes in the mother to be able to deliver her fetus through the birth canal. This study aims to determine the effect of Perineal Massage in Trimester III Pregnant Women on the Incidence of Perineal Rupture during Childbirth at the Yusmalinda Clinic, Stabat District, Langkat Regency in 2022. The population in this study were all pregnant women who were pregnant in TM III, gestational age 34-36 weeks before delivery of 40 people. the sample in this study were 40 people, that there was an effect of perineal massage in third trimester pregnant women on the incidence of perineal rupture during childbirth at the Yusmalinda Clinic, Stabat District, Langkat Regency, p value = 0.0003. p value = 0.000 (P > 0.05) this means that there is an effect of perineal massage in third trimester pregnant women on the incidence of perineal rupture during childbirth at the Yusmalinda Clinic, Stabat District, Langkat Regency.